Importance of intact secondary protein structures of cell envelopes and glass transition temperature of the stabilization matrix on the storage stability of probiotics. (September 2019) - Nag, Arup; Waterland, Mark; Janssen, Patrick; Anderson, Rachel; Singh, Harjinder
Abstract: Lactobacillus reuteri LR6 cells were stabilized using a novel combination of wet granulation and fluidized-bed-drying techniques. The stabilized cells were stored at 37 °C and at two water activity (aw ) levels (0.11 & 0.30). Superior storage stability was recorded in the lower aw environment, supported by a stronger glassy matrix when skim milk powder was used as the excipient. The initial viable cell populations of the samples stabilized in different matrices ranged from 8.3 to 9.1 log CFU/g. At the end of the storage period, the viable cell populations were reduced to 6.7 to 7.3 log CFU/g at aw 0.11 and to 6.1 to 6.6 CFU/g when the aw was maintained at 0.30. Fourier transform infrared spectroscopic examination of the cell envelopes revealed substantial dissimilarities between samples at the beginning and at the end of the storage period, which indicated alteration in the secondary protein structures of the cell envelope and also correlated well with the loss in cell viability. In milk-powder-based matrices, adjusting the aw to 0.30 resulted in a weaker or no glassy state whereas the same matrices had a high glass transition temperature at aw 0.11. This strong glassy matrix and low aw combination was found to enhance the bacterial stability at the storage temperature of 37 °C. Scanning electron microscopy revealed the formation of corrugated surfaces and blister-type deformations on the cell envelopes during the stabilization process. Graphical abstract: Unlabelled Image Highlights: Superior storage stability of probiotics at 37 °C was observed at aw 0.11 over aw 0.30. Milk based matrices and polyol coating yielded higher Tg and found responsible for better stability. FTIR analysis revealed substantial alterations in the membrane protein structures during storage. The said alterations were directly correlated with cell death during storage period. SEM images confirmed visual damages to the cell membrane during desiccation and storage.